CD73 regulates zoledronate-induced lymphocyte infiltration in triple-negative breast cancer tumors and lung metastases - Petruk, Nataliia; Siddiqui, Arafat; Tadayon, Sina; Määttä, Jorma; Mattila, Pieta K.; Jukkola, Arja; Sandholm, Jouko; Selander, Katri S. (Frontiers in Immunology, 2023)
Bisphosphonates (BPs) are bone-protecting osteoclast inhibitors, typically used in the treatment of osteoporosis and skeletal complications of malignancies. When given in the adjuvant setting, these drugs may also prevent relapses and prolong overall survival in early breast cancer (EBC), specifically among postmenopausal patients. Because of these findings, adjuvant nitrogen-containing BPs (N-BPs), such as zoledronate (ZOL), are now the standard of care for high-risk EBC patients, but there are no benefit-associated biomarkers, and the efficacy remains low. BPs have been demonstrated to possess anti-tumor activities, but the mechanisms by which they provide the beneficial effects in EBC are not known. In this study, we compared ZOL effects on tumor growth and tumor-infiltrating lymphocytes (TILs) using 4T1 breast cancer cells together with suppression of CD73 (sh-CD73). Sh-CD73 4T1 cells were significantly more sensitive to the growth inhibitory effects of n-BPs in vitro. However, while ZOL-induced growth inhibition was similar between the tumor groups in vivo, ZOL enhanced B and T lymphocyte infiltration into the orthotopic tumors with down-regulated CD73. A similar trend was detected in lung metastases. ZOL-induced tumor growth inhibition was found to be augmented with B cell depletion in sh-NT tumors, but not in sh-CD73 tumors. As an internal control, ZOL effects on bone were similar in mice bearing both tumor groups. Taken together, these results indicate that ZOL modifies TILs in breast cancer, both in primary tumors and metastases. Our results further demonstrate that B cells may counteract the growth inhibitory effects of ZOL. However, all ZOL-induced TIL effects may be influenced by immunomodulatory characteristics of the tumor.